Totalitarianism and hostility as anthropological and spiritual wounds - Platovnjak, Ivan (Bogoslovni vestnik, 2025)
This article argues that hatred, as seen in totalitarian regimes and contemporary social fragmentation, is a profound anthropological and spiritual wound. Drawing on the works of Hannah Arendt and Simone Weil, this exploration examines how dehumanization, ideological illusion, and thoughtlessness erode moral responsibility and contribute to systemic evil. Arendt highlights the collapse of judgment in totalitarianism; Weil examines how force, illusion, and spiritual disconnection nourish hatred. In response, the article proposes Christian spirituality as a transformative path: not a private refuge but a source of critical awareness, inner freedom, and social responsibility. Through spiritual discernment and solidarity, individuals can resist hatred and rebuild fraternity. This interdisciplinary dialogue between political philosophy and spirituality provides a holistic framework for addressing hostility and fostering peace.
Keywords: Arendt, Hannah; Christianity; duhovnost; hatred; krščanstvo; mir; peace; sovraštvo; spirituality; Weil, Simone